Study on Economic Benefits of Electric Vehicle Battery Swapping Station Participating in Power Market Auxiliary Service - Jie LI; Bing YANG (Zhongguo dianli)
The battery swapping mode can improve the operation efficiency of electric vehicles(EVs) and achieve better interaction with power grid. This paper took the EVs battery swapping station as the research object, analyzed the operation mode of the station, established an energy conservation model and an economic income model, and explored the feasibility and potential of improving the economic income of the exchange station via auxiliary service in power market. Then, the influence of key factors such as battery parameters and battery ratio on the revenue was analyzed. The results show that, only by increasing the number of batteries in the station, the revenue cannot be effectively improved. However, when the per kilowatt hour cost of the power battery is reduced by about 10% or the number of cycles is increased by about 15%, the investment income balance can be realized, and the impact of increasing the cycle times of power battery is greater than that of reducing the price of kilowatt hour.